Análise morfométrica da série molar inferior em Didelfídeos (Mammalia) - Magnus, Luíza Zuchetto (2014)
Tribosphenic molars are considered major innovations of mammals and are related to different structures and variables that may explain their adaptation. The aim of this study was to verify the relationship of body size, mandible shape and diet variables and all four molars of didelphid marsupials in a phylogenetic approach. Geometric morphometric analysis of shape of the lower molars were performed on 261 specimens, 130 females and 131 males, containing a total of 14 genera and 37 species of the Didelphidae family. Twenty- four anatomical landmarks were used to describe the shape of the molars, and twenty-three for the mandible. The body size was estimated from values of molar size (lnCS) and diet was categorized through the literature. All analyzes were performed separately for males and females due to sexual dimorphism. Regressions were performed between the shape of molars and the explanatory variables body size, mandible shape and diet. An analysis of Variation Partitioning was applied to test the explanation portion of each variable. The phylogenetic effect on shape was controlled in such analyses with the method of phylogenetic generalized least squares (PGLS). For females the diet has a major influence on the molars (30.1%), followed by body size (9.3%) and mandibular shape (2.7%), whereas for males the diet has also a lot of influence (31.4%), body size (10.3%) and mandibular shape (28.5%). The configuration of molars due to diet showed greater deformity in a gradient, showing increased size from the first to the fourth molar area (greater m4) for more faunivorous/omnivorous species and, contrarily, a decrease in size toward the lower m4 for frugivorous/omnivorous species. Variation Partitioning in the diet was more explanatory for females (18.6%) and mandibular shape (13.8%); and the interaction of mandibular shape with diet was more important for males (19.3%). The explanation of diet for both sexes, although significant, has a strong influence of phylogenetic relatedness, while both mandibular shape and body size for males show no such influence of phylogeny. The great difference in the results for both sexes highlights the importance of life style influencing differentially females and males. The variation of the non-uniform molar shape exposes what is already seen in the literature: that didelphids have not a fully exclusive diet. Thus, it is possible to realize the importance of molars in both function and phylogenetic history.